ANALYSIS OF THE PROBLEMS OF DEVELOPING CHILDREN'S TALENTS IN SPECIALIZED SCHOOLS AND THEIR STATE OF PRACTICE (American Journal of Pedagogical and Educational Research, 2025)
This article describes the analysis and current state of the problems of the development of children's talent in specialized schools. Also, the theoretical analysis carried out in the study made it possible to determine the evolution of ideas about the problem of the development of children's talent in historical and modern conditions and the dynamics of its development. The theoretical analysis carried out in the study made it possible to determine the evolution of ideas about the problem of the development of children's talent in historical and modern conditions and the dynamics of its development.